2008
DOI: 10.1111/j.1600-6143.2008.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor HLA-C Genotype Has a Profound Impact on the Clinical Outcome Following Liver Transplantation

Abstract: Late allograft dysfunction is a significant problem following liver transplantation and its pathogenesis is uncertain. HLA-C is the major inhibitory ligand for killer immunoglobulin-like receptors (KIRs) that regulate the cytotoxic activity of natural killer (NK) cells. HLA-C alleles can be allocated into two groups, termed HLA-C1 and HLA-C2, based on their KIR specificity. HLA-C2 interactions are more inhibiting to NK cell activation. We studied the clinical importance of HLA-C genotype in a large liver trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 43 publications
7
52
1
Order By: Relevance
“…on May 12, 2018. by guest www.bloodjournal.org From impact on the outcome of liver transplants. 65 HLA-C is the major inhibitory ligand for killer cell immunoglobulin-like receptors (KIRs). KIR genes are highly polymorphic and are expressed on natural killer cells and a subset of T lymphocytes.…”
Section: Org Frommentioning
confidence: 99%
“…on May 12, 2018. by guest www.bloodjournal.org From impact on the outcome of liver transplants. 65 HLA-C is the major inhibitory ligand for killer cell immunoglobulin-like receptors (KIRs). KIR genes are highly polymorphic and are expressed on natural killer cells and a subset of T lymphocytes.…”
Section: Org Frommentioning
confidence: 99%
“…12,27 Another study showed significantly decreased graft survival in the presence of 0 or 1 mismatch compared with 2 HLA-DR mismatches, with decreased risk for developing recurrent primary sclerosing cholangitis with 2 HLA-DR mismatches. 26 It has been hypothesized that human leukocyte antigen mismatching may act beneficially by decreasing the effects of immunologic mechanisms associated with disease recurrence in patients transplanted for autoimmune diseases. 40 The human leukocyte antigen mismatching at all loci positively affects patients transplanted for autoimmune hepatitis, 41 and a negative effect of DR mismatching has been noted on graft survival in patients with autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed an effect of HLA-C on chronic rejection and graft loss. 26 The HLA-C alleles may be important as ligands for killer immunoglobulinlike receptors. These receptors are present on NK cells and some T lymphocytes and may affect cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While recognition of HLA mismatch by T cells is well established as the main driver of graft rejection in other solid organ transplants, HLA cross-matching is not normally performed prior to LT. Any role for HLA matching in LT remains controversial. Early studies of HLA-C disparity between donor and recipient showed correlation between HLA-C matching, reduction in acute rejection rate, and increased graft survival (35,36). Increased expression of the KIR2D receptors on recipient NK cells, which is responsible for the recognition of HLA-C epitopes, also correlated with increased graft survival and fewer episodes of rejection (37).…”
Section: Nk Cells In Rejectionmentioning
confidence: 99%